Adverse effects of trazodone in dogs on primary hemostasis and electrocardiogram: A single‐blinded placebo‐controlled crossover study - Eduardo J. Benjamin; O. Lynne Nelson; Ryan Baumwart; Jillian Haines (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Trazodone is a serotonin antagonist/reuptake inhibitor medication commonly used for anxiety in dogs. Therapy with selective serotonin reuptake inhibitors in humans is associated with bleeding disorders and increased arrhythmogenesis. Hypothesis/Objectives To evaluate markers of primary hemostasis and corrected QT (cQT) interval in dogs before and after oral administration of standard dosages of trazodone or placebo. Animals Fifteen apparently healthy, client‐owned dogs. Methods A single‐blinded, randomized placebo‐controlled crossover study was performed. Dogs were administered trazodone (5 to 7.5 mg/kg PO Q12h) or placebo. [Correction added after first online publication on 14 October 2023. In the abstract (methods) section (57.5 mg/kg PO Q12h) changed as (5 to 7.5 mg/kg PO Q12h).] Buccal mucosal bleeding time (BMBT), platelet count, platelet aggregation via Plateletworks, PFA‐100 closure time and cQT interval were measured. A Shapiro‐Wilk test was performed followed by either a paired t test or a Wilcoxon signed‐rank test. Results No significant difference was detected in the BMBT, PFA‐100 closure times, platelet counts, and cQT interval between trazodone or placebo. However, using Plateletworks, there was a significant decrease in platelet aggregation after administration of trazodone (95%; 81‐97 vs 62%; 39‐89, P = .002) and not placebo (95%; 81‐97 vs 91%; 81‐96, P = .21). Conclusions It is unknown if this represents a clinically relevant change or if dogs with preexisting impairment in primary hemostasis or receiving higher dosages or longer durations of trazodone could have a more substantial change in hemostatic variables.